(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article is devoted to information technologies in the educational system, it is written about the issues of reforming and improving the continuous education system of our country, raising it to a new level of quality, introducing advanced pedagogical and information technologies to it, and increasing the effectiveness of education